Anti-androgenic activities of diuron and its metabolites in male Nile tilapia (Oreochromis niloticus) - Pereira, Thiago Scremin Boscolo [UNESP]; Boscolo, Camila Nomura Pereira [UNESP]; Silva, Danilo Gruenig Humberto da [UNESP]; Batlouni, Sergio Ricardo [UNESP]; Schlenk, Daniel; Almeida, Eduardo Alves de [UNESP] (Elsevier B.V., 2015)
Diuron (3-(3,4-dichlorophenyl)-1,1-dimethylurea) is a widely used herbicide which has been frequently detected in surface waters throughout the world. In vivo bioassay guided fractionation studies indicated that diuron may have estrogenic activity augmented by biotransformation. This study evaluated the effects of diuron and three of its metabolites on plasma hormone concentrations and spermatogenesis of the freshwater fish Nile tilapia (Oreochromis niloticus). Sexually mature male fish were exposed for 25 days to diuron, as well to its metabolites 3,4-dichloroaniline (DCA), 3,4-dichlorophenylurea (DCPU) and 3,4-dichlorophenyl-N-methylurea (DCPMU), at concentrations of 200 ng/L. Testosterone levels were decreased by diuron, but had limited effects on gonadal histology. Diuron metabolites, however, caused significant decreases in testosterone and in 11-ketotestosterone, gonadosomatic index, diameter of seminiferous tubules and in the mean percentages of germ cells (spermatids and spermatozoa). We conclude that these metabolites have antiandrogenic activity to male Nile tilapia, potentially causing reproductive impairment in male fish.
Keywords: Nile tilapia; Gametogenesis; Diuron; Diuron metabolites; Andi-androgenic effects